2014
DOI: 10.1111/pce.12454
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen supply to thermogenic flowers

Abstract: Thermogenic flowers produce heat by intense respiration, and the rates of O2 consumption (Ṁo2) in some species can exceed those of all other tissues of plants and most animals. By exposing intact flowers to a range of O2 pressures (Po2) and measuring Ṁo2, we demonstrate that the highest respiration rates exceed the capacity of the O2 diffusive pathway and become diffusion limited in atmospheric air. The male florets on the inflorescence of Arum concinnatum have the highest known mass-specific Ṁo2 and can be se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…However, if Ṁ o 2 depends on Po 2 near 21 kPa, then the system is diffusion‐limited, and some mitochondria are normally not O 2 saturated. Our experiments have indicated that some moderately thermogenic species are not diffusion‐limited, but the most thermogenic species are (Seymour, Ito, Umekawa, Matthews, & Pirintsos, ). In particular, Ṁ o 2 of inflorescences of the Japanese skunk cabbage Symplocarpus renifolius declines at all Po 2 levels below 21 kPa in the most thermogenic individuals (i.e.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, if Ṁ o 2 depends on Po 2 near 21 kPa, then the system is diffusion‐limited, and some mitochondria are normally not O 2 saturated. Our experiments have indicated that some moderately thermogenic species are not diffusion‐limited, but the most thermogenic species are (Seymour, Ito, Umekawa, Matthews, & Pirintsos, ). In particular, Ṁ o 2 of inflorescences of the Japanese skunk cabbage Symplocarpus renifolius declines at all Po 2 levels below 21 kPa in the most thermogenic individuals (i.e.…”
Section: Introductionmentioning
confidence: 84%
“…If the respiratory quotient (Ṁ co 2 /Ṁ o 2 ) in S. renifolius is approximately 1.0, as it is in S. foetidus (Seymour & Blaylock, ), the previous Ṁ CO 2 data correspond well with the present data. In further experiments on S. renifolius designed to test for diffusion limitation by varying ambient Po 2 , Ṁ o 2 varied between 117 and 356 nmol O 2 s −1 g −1 when T s was 15 °C and Po 2 was 20.9 kPa (Seymour et al, ). Two inflorescences with the lowest Ṁ o 2 (117 and 148 nmol O 2 s −1 g −1 ) did not appear to be diffusion‐limited, because the regression of Ṁ o 2 on Po 2 nearly plateaued (98% asymptotic) at 20.9 kPa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that Ala adequately mimics dehydro-Ala in the THI4 active site, these results indicate that C. bicolor THI4 could function catalytically in male flower tissue after an initial suicide reaction, provided that the oxygen level is low and the sulfide level is relatively high. Aroid spadices are known to become internally hypoxic at the flowering (thermogenic) stage (Seymour et al, 2015), and classical data on oxygen consumption rates indicate that they also may be hypoxic at earlier stages when tightly wrapped in the spathe (James and Beevers, 1950;Seymour et al, 1984). As noted above, sulfide levels in plant tissues may exceed those in E. coli.…”
Section: Bicolor Thi4 May Retain Catalytic Activity After Loss Of mentioning
confidence: 98%